Semantic correlations of Belarusian-otherslavic lexical parallels in etymological word family (based on one type of word family *lik- derivatives) - Branavets, Pavel S. (Journal of the Belarusian State University. Philology, 2021)
Based on lexicographic data, there are presented 50 Belarusian-otherslavic (Ukrainian, Russian, Polish and Czech) lexical parallels, which are the part of the etymological word family of the Proto-Slavic root *lik-, with the restriction of selection to derived verbs like ад-лічыць (від-лічити, от-личить, od-liczyć, od-líčit). The types of their semantic relations are considered: homosemy, parasemy, heterosemy. Three types of relations corresponding to a gradual transition from homosemic to heterosemic (stylistic-connotative decorelation, semantic inclusion, semantic intersection) are identified among parasemants. Strong and weakened cases are proposed to be distinguished in heterosemy. Based on qualitative and quantitative comparison, the conclusion was made about the greatest semantic rapprochement of the Belarusian sample with the Ukrainian, the smallest one with the Russian. Factors influencing the folding of the type of semantic relations are named. Hypothesis on typological role of character of semantic correlation of etymologically connected interlingual lexical parallels in comparing of closely related languages lexicons is proposed. Lexical parallels given separately by language can be used as fragments of contrastive dictionaries during studying the corresponding languages or translation practice.